Energy Cost of Force Production After a Stretch-Shortening Cycle in Skinned Muscle Fibers: Does Muscle Efficiency Increase? - Joumaa, Venus; Fukutani, Atsuki; Herzog, Walter (Frontiers in Physiology, 2021)
Muscle force is enhanced during shortening when shortening is preceded by an active stretch. This phenomenon is known as the stretch-shortening cycle (SSC) effect. For some stretch-shortening conditions this increase in force during shortening is maintained following SSCs when compared to the force following a pure shortening contraction. It has been suggested that the residual force enhancement property of muscles, which comes into play during the stretch phase of SSCs may contribute to the force increase after SSCs. Knowing that residual force enhancement is associated with a substantial reduction in metabolic energy per unit of force, it seems reasonable to assume that the metabolic energy cost per unit of force is also reduced following a SSC. The purpose of this study was to determine the energy cost per unit of force at steady-state following stretch-shortening cycles and compare it to the corresponding energy cost following pure shortening contractions of identical speed and magnitude. We hypothesized that the energy cost per unit of muscle force is reduced following SSCs compared to the pure shortening contractions. For the SSC tests, rabbit psoas fibres (n=12) were set at an average sarcomere length (SL) of 2.4 µm, activated, actively stretched to a SL of 3.2 µm, and shortened to a SL of 2.6 µm or 3.0 µm. For the pure shortening contractions, the same fibres were activated at a SL of 3.2 µm and actively shortened to a SL of 2.6 µm or 3.0 µm. The amount of ATP consumed was measured over a 40s steady-state total isometric force following either the SSCs or the pure active shortening contractions. Fibre stiffness was determined in an additional set of twelve fibres, at steady-state for both experimental conditions. Total force, ATP consumption, and stiffness were greater following SSCs compared to the pure shortening contractions, but ATP consumption per unit of force was the same between conditions. These results suggest that the increase in total force observed following SSCs was achieved with an increase in the proportion of attached cross-bridges and titin stiffness. We conclude that muscle efficiency is not enhanced at steady-state following SSCs.